Antibacterial Activity Test of the C-4-methoxyphenylcalix[4]resorcinarene Compound Modified by Hexadecyltrimethylammonium-Bromide against Staphylococcus aureus and Escherichia coli Bacteria - Suryadi Budi Utomo; Mita Fujiyanti; Warih Puji Lestari; Sri Mulyani (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2018)
This study aims to determine the antibacterial activity of C-4-methoxyphenylcalix-[4]resorcinarene modified by Hexadecyltrimethylammonium-Bromide (Resorcinarene-HDTMA-Br) against Staphylococcus aureus and Escherichia coli bacteria. The study was conducted by testing the inhibition zone diameter with paper disc diffusion method. Variations in the concentration of the sample used were 10%; 15%; 20%; 25%; and 30% b/v. In this study, Dimethyl sulfoxide (DMSO) (sampel solvent) was used as a negative control and Chloramphenicol as a positive control. It was found that Resorsinarene-HDTMA-Br had higher antibacterial activity than the unmodified C-4-methoxyphenylcalix[4]resorcinarene (CMFKR) against the S. aureus bacteria. Both CMFKR and Resorcinarene-HDTMA-Br are not active against E. coli.